2012
DOI: 10.1016/j.bbabio.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The PsbQ protein stabilizes the functional binding of the PsbP protein to photosystem II in higher plants

Abstract: PsbP and PsbQ proteins are extrinsic subunits of photosystem II (PSII) and optimize the oxygen evolution reaction by regulating the binding properties of the essential cofactors Ca(2+) and Cl(-). PsbP induces conformational changes around the catalytic Mn cluster required for Ca(2+) and Cl(-) retention, and the N-terminal region of PsbP is essential for this reaction. It was reported that PsbQ partially restores the functional defect of N-terminal truncated PsbP [Ifuku and Sato (2002) Plant Cell Physiol. 43, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…2 A and B). Our identification of interacting domains between PsbP and PsbQ helps explain the observation that PsbQ assists in the stabilization of PsbP binding and function (32,33). This observation may also explain why loop 3A is disordered and not resolved in the current PsbP crystal structure.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…2 A and B). Our identification of interacting domains between PsbP and PsbQ helps explain the observation that PsbQ assists in the stabilization of PsbP binding and function (32,33). This observation may also explain why loop 3A is disordered and not resolved in the current PsbP crystal structure.…”
Section: Resultsmentioning
confidence: 52%
“…An N-terminal 19-amino-acid residue-truncated PsbP cannot bind to PS II in the absence of PsbQ but can bind in its presence. Importantly, in the presence of PsbQ, the function of the truncated PsbP is partially restored (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that H144A cannot restore this conformational change (20). Because H144A showed a defect in Cl Ϫ retention in PSII, the conformational change induced by PsbP would be relevant to Cl Ϫ binding in PSII.…”
Section: D165v Mutation Of the H144a Mutant Psbp Protein Restored Thementioning
confidence: 98%
“…The PsbP and PsbQ proteins in green plants seem to have evolved from their cyanobacterial homologs, although considerable genetic and functional modifications seem to have occurred to generate the eukaryote-type PsbP (16,17). The locations and binding topologies of PsbP and PsbQ in the green plant PSII complex have been proposed (17,18) (19,20). Truncation of the PsbP N terminus by 15 residues resulted in a loss of the protein Ca 2ϩ and Cl Ϫ retention ability (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation